2015
DOI: 10.1371/journal.pone.0120698
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-30c Targeting ADAM19 in Colorectal Cancer

Abstract: MicroRNAs (miRNAs) are deregulated in a number of cancers including colorectal cancer. MiR-30c belongs to miR-30 family, and is involved in a variety of malignant diseases. In this study, we detected the expression of miR-30c in colon cancer cell lines and clinical colon cancer specimens. MiR-30c was shown to be dramatically down-regulated both in cell lines and cancer tissues. Additionally, miR-30c could inhibit cancer cell growth, migration and invasion in vitro. Consistently, stable over-expression of miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 41 publications
2
39
0
2
Order By: Relevance
“…The cell proliferation assay was performed using a standard procedure [17]. For the colony formation assay, 1000 cells/well were seeded in a 6-well plate in 2 mL complete media for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…The cell proliferation assay was performed using a standard procedure [17]. For the colony formation assay, 1000 cells/well were seeded in a 6-well plate in 2 mL complete media for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…miR-30a promotes tumorigenesis in these cancers by directly targeting tumor-associated proteins. Zhang et al (24) demonstrated that miR-30c inhibited the growth and lung metastasis of colon cancer by targeting ADAM metallopeptidase domain 19. miR-30a has also been reported to target insulin receptor substrate 2 in colorectal tumorigenesis (18). However, the expression and role of miR-30a in the progression of cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-30e negatively regulates BIRC6 and AVEN, which suppresses the apoptotic activity and it also inhibits Beclin-1 and suppress autophagic process in glioblastoma cell lines [55]. MiR-30c is the member of miR-30 family which inhibited the progression of colon cancer growth by regulating ADAM-19 gene expression [56]. MiR-30c targets several multifaceted cancer associated genes UB69, MTA1 and HBOX1 in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are main regulators of NF-kB pathway where miR-30e directly target and abrogates the functions of IkBα, a potential inhibitor of NF-kB in prostate cancer. Moreover, miR-30e and miR-30c are evolutionary conserved in varies vertebral species [59,60,56]. In ovarian cancer cells, miR-30c-2-3p targets Activating Transcription Factor 3 (ATF-3) and induces cell proliferation that leads to cancer progression [61].…”
Section: Discussionmentioning
confidence: 99%